On the Convergence of King-Werner Iteration Method in Banach Space (Journal of Computational Mathematics, 2000)
In this paper, a Kantorovitch-Ostrowski type convergence theorem and an error estimate of $\frac{\|f'(z_0)^{-1}f(x_{n+1})\|}{\|f'(z_0)^{-1}f(x_n)\|}$ using the information of higher derivatives at the center between initial points for King-Werner iteration method in Banach space are established.
Keywords: Information at the center between initial points; King-Werner iteration method; Convergence; Error estimate.